The Correlation Value of DAS28 with Anti-CCP Titer on Rheumatoid Arthritis Patients in Cipto Mangunkusumo Hospital in 2012-2016 - Harry Isbagio; Deka Yuli Fadillah (Indonesian Journal of Rheumatology, 2018)
Background: Rheumatoid Arthritis (RA) is one of the diseases associated with the immune system which causes joint damage and effect to the quality of patient’s life. DAS28 CRP value describes RA disease activity. The anti-CCP titer is a very specific examination which provide an overview prognosis of RA patient’s illness. The research on the correlation of anti-CCP Titers with DAS28 CRP values has never been done in Indonesia. Therefore, this research aims to determine the correlation between anti-CCP Titer and DAS28 CRP value in RA patient in Cipto Mangunkusumo hospital with DAS28 CRP value in RSCM. Method: The research design is cross-sectional with the sample amounted to 34. anti-CCP and DAS28 CRP were obtained through patient’s medical records.Result The result of this correlationstudy is (p = 0,582) and r = 0,086. Conclusion: In conclusion, there is no correlation between anti-CCP and DAS28 in Cipto Mangunkusumo hospital. Keywords: Anti-CCP; DAS28 CRP; Rheumatoid Arthritis